Antibiotic susceptibility of Helicobacter pylori strains isolated from Iranian children: High frequency of A2143G point mutation associated with clarithromycin resistance. (September 2017) - Mahmoudi, Shima; Mamishi, Setareh; Banar, Maryam; Keshavarz Valian, Sepideh; Bahador, Abbas; Najafi, Mehri; Farahmand, Fatemeh; Pourakbari, Babak
Highlights: The antibiotic resistance of H. pylori is rising in developing countries. In our study, the prevalence of H. pylori infection among children was 35.5% (32 positive cultures out of 90 biopsy specimens). The resistance rate to CLR was 21.8%, which was higher than the resistance rate detected by other studies in Iran. The A2143G point mutation was detected in 71% of CLR resistant isolates (5 out of 7 CLR resistant isolates). Abstract: Objective: Increasing antibiotic resistance in Helicobacter pylori is a global concern and is associated with treatment failure. The aim of this study was to evaluate antibiotic resistance of H. pylori to different antibiotics including amoxicillin, erythromycin, ciprofloxacin, furazolidone, tetracycline, metronidazole and clarithromycin. In addition, ​detection of A2143G mutation in clarithromycin resistant isolates was performed using real-time PCR technique. Methods: Ninety patients with upper gastrointestinal symptoms were enrolled in this study. H. pylori were isolated from 32 specimens and the resistance rate of these strains to amoxicillin, erythromycin, ciprofloxacin, furazolidone, and tetracycline was tested by disc agar diffusion method. The resistance level to metronidazole and clarithromycin was determined by agar dilution method. The presence of A2143G point mutation in clarithromycin resistant isolates was determined using real-time PCR technique. Results: The resistance rates to amoxicillin, erythromycin, ciprofloxacin, furazolidone, tetracycline, metronidazole and clarithromycin were 53%, 50%, 37.5%, 62.5%, 25%, 62.5% and 22%, respectively. The A2143G point mutation was detected in 71% of clarithromycin resistant strains (5 out of 7). Conclusions: The prevalence of H. pylori resistance to metronidazole, ciprofloxacin, erythromycin, amoxicillin and furazolidone in Iran is high. Determination of antibiotic susceptibility plays an important role in selecting of the appropriate anti H. pylori regimen.